2021
DOI: 10.21037/qims-20-538
|View full text |Cite
|
Sign up to set email alerts
|

An efficient deep convolutional neural network model for visual localization and automatic diagnosis of thyroid nodules on ultrasound images

Abstract: Background:The aim of this study was to construct a deep convolutional neural network (CNN) model for localization and diagnosis of thyroid nodules on ultrasound and evaluate its diagnostic performance. Methods:We developed and trained a deep CNN model called the Brief Efficient Thyroid Network (BETNET) using 16,401 ultrasound images. According to the parameters of the model, we developed a computer-aided diagnosis (CAD) system to localize and differentiate thyroid nodules. The validation dataset (1,000 images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Finally, the all included studies used the deep learning VGGNet model. The 11 sets of data from eight papers used the deep learning VGG-16 models (7,14,(19)(20)(21)(22)(23)25), and 6 sets of data from four papers used the deep learning VGG-19 models Moreover, the performance of the DL model is closely connected with the number of training data, and the DL model performs better when the data of the training sample are sufficiently large (36). Based on an analysis of 11 included studies, 2 sets of data from three papers did not give an explicit number of training sets, 14 sets of data from eight papers did give the number of training sets, but the amount of pre-training varied across studies and the amount of learning varied; thus, it is difficult to know the overfitting results of the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the all included studies used the deep learning VGGNet model. The 11 sets of data from eight papers used the deep learning VGG-16 models (7,14,(19)(20)(21)(22)(23)25), and 6 sets of data from four papers used the deep learning VGG-19 models Moreover, the performance of the DL model is closely connected with the number of training data, and the DL model performs better when the data of the training sample are sufficiently large (36). Based on an analysis of 11 included studies, 2 sets of data from three papers did not give an explicit number of training sets, 14 sets of data from eight papers did give the number of training sets, but the amount of pre-training varied across studies and the amount of learning varied; thus, it is difficult to know the overfitting results of the model.…”
Section: Discussionmentioning
confidence: 99%
“…From then on, deep learning entered an era of rapid development and played a pivotal role in the medical field, especially in medical image recognition. Some studies used the deep learning convolutional neural network to extract ultrasound features to identify and diagnose benign and malignant thyroid nodules, and some of the studies with diagnostic performance could be comparable to or better than the advanced physicians, which could reduce unnecessary punctures and overtreatment, and help grassroots and inexperienced physicians improve diagnostic efficiency and accuracy (5)(6)(7). In addition, Lee et al (8) explored the use of deep learning convolutional neural networks in predicting the presence of lymph node metastasis in thyroid cancer on ultrasound, and their results indicated good predictive diagnostic accuracy (accuracy of 83.0%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also provided 159 video datasets and we have made them publicly available (https://drive.google.com/ drive/folders/1cP25UNROveiafvumT9vInQ2OQj3xdug?usp=sharing) so that more researchers can participate in improving and clinically verifying this method. In the future, we hope to expand and improve this computing framework through deep learning, artificial intelligence, and image segmentation (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…To acquire a decent performance, we chose the visual geometry group (VGG) deep CNN [33] since we observed that it does not include a global average pooling layer after the last feature extraction layer but directly flattens the feature maps and connects them with three fully connected layers sequentially, which may lead to better diagnostic performance as all extracted significant features are weighted. Indeed, VGG has demonstrated convincing classification accuracy in various medical image analysis tasks [17,[34][35][36][37], including breast mass classification [32,38,39]. The VGG-19 architecture was adopted as the backbone for breast cancer diagnosis modeling in this study.…”
Section: Deep Learningmentioning
confidence: 99%